1997
DOI: 10.1176/ajp.154.2.274
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive-compulsive disorder with and without tics in an epidemiological sample of adolescents

Abstract: O bsessive-compulsive disorder is a common disorder, with a lifetime prevalence in adolescence of 2%-3% (1, 2). The rising frequency of diagnosis of obsessive-compulsive disorder over the last decade (3) has motivated researchers to distinguish subtypes of obsessive-compulsive disorder. Several studies (4-6 and unpublished study by V. Eapen et al.) have compared adult patients with obsessive-compulsive disorder with and without chronic tic disorder or Gilles de la Tourette's disorder on the content of their ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…The miscellaneous compulsions of the type reported in this study were also reported in previous studies of OCD patients with tics[100101] but the obsessions are not similar to the ones reported in other studies that found mainly excess of aggressive, sexual, and symmetry obsessions. [101102] Further, the elevated rate of ADHD in juvenile OCD with tics support the previous observations that ADHD, tics and OCD commonly co-occur in juvenile OCD[99103] and are possibly interrelated sharing a common pathophysiology. [104]…”
Section: Ocd In Children and Adolescentssupporting
confidence: 67%
“…The miscellaneous compulsions of the type reported in this study were also reported in previous studies of OCD patients with tics[100101] but the obsessions are not similar to the ones reported in other studies that found mainly excess of aggressive, sexual, and symmetry obsessions. [101102] Further, the elevated rate of ADHD in juvenile OCD with tics support the previous observations that ADHD, tics and OCD commonly co-occur in juvenile OCD[99103] and are possibly interrelated sharing a common pathophysiology. [104]…”
Section: Ocd In Children and Adolescentssupporting
confidence: 67%
“…[56,60,62,71-73] Tic-related OCD is highly familial. [56,59-61,74] For example, Rosario-Campos et al [61] studied 325 first-degree relatives of 106 children and adolescents with early-onset OCD (<18 yrs) and found that when the OCD probands were stratified according to presence of a comorbid chronic tic disorder, the case-relatives of the probands with a chronic tic disorder had a significantly higher recurrence risk of OCD: 23.8% (probands with a tic disorder) versus 14.9% (probands without a tic disorder). They also reported that a comorbid diagnosis of tics in the relatives was the best predictor of a diagnosis of OCD (OR = 7.35; 95% CI: 3.79–14.25, P <.0001).…”
Section: Resultsmentioning
confidence: 99%
“…Whether these differences are clinically meaningful is unclear, especially when compared to prior data that reveal no consistent pattern of OCD content in those with tic-related OCD. 9-11 The convergence of findings seems to suggest that tic-related OCD is not indicative of particular OCD symptom profiles. Clinically, this highlights the importance of not making broad assumptions about the type of OCD symptoms most likely to occur in an individual with comorbid tics.…”
Section: Discussionmentioning
confidence: 98%
“…Zohar et al 9 reported that obsessional content discriminated adolescents with tic-related OCD from adolescents with OCD, in that those with tic-related OCD endorsed more aggressive obsessions while others in the sample endorsed more sexual obsessions. In contrast, in a sample of children and adolescents, 10 topography of compulsions, but not obsessions, discriminated those with tic-related OCD.…”
Section: Introductionmentioning
confidence: 99%